Virulence and hostpathogen interaction of Botryodiplodia theobromae isolates of cassava root rot disease - Onyeka, T.; Ekpo, E.; Dixon, A. (Wiley, 2005)
Pathogenic variation of Botryodiplodia theobromae, the cause of cassava root rot disease in Nigeria, was evaluated with 84 isolates from three different ecological zones and four genetically diverse cassava genotypes using root slice inoculation assay. Significant variation was observed for the aggressiveness of isolates, resistance of cassava genotypes and isolate–genotype interactions for percentage diseased area. The isolate effect accounted for 32.13% of total variation, 38.60% was due to genotype effect and 29.16% due to isolate–genotype interactions. The virulence distribution of the pathogen isolates on each of the cassava genotypes showed that 11.36% of the isolates were highly virulent on 30572, 27.27% on 91/02324, 67.05% on TME-1 and 90.91% on 92/0057. Biplot and joint regression analysis confirmed that the isolates varied significantly in their aggressiveness, and there was a quantitative differential interaction between B. theobromae isolates and cassava genotypes for percentage diseased area of inoculated root slice. However, there was relative consistency in the virulence classification of the isolates on resistant and susceptible controls.